Sustainable Self-Compacting Concrete: The Role of Limestone Powder as A Cement Replacement - Muhammad Ramdhan Olii; Andi Aswin Rahman; Nasir Bumulo; Rahman Abdul Djau; Ilyas Ichsan (Departement of Civil Engineering, Universitas Winaya Mukti, 2026)
The excessive use of cement in concrete production contributes significantly to environmental impacts, particularly CO? emissions. One potential solution is the partial replacement of cement with limestone powder in self-compacting concrete (SCC). This study aimed to investigate the effect of limestone powder as a partial cement replacement on the fresh properties and compressive strength of SCC. Limestone powder was used at replacement levels of 0%, 6%, 9%, 12%, and 15% by weight of cement. The fresh properties of SCC were evaluated using slump flow, V-funnel, and L-box tests, while compressive strength tests were conducted to assess hardened performance. The results showed that SCC mixtures containing up to 9% limestone powder satisfied the SCC workability requirements. The optimum performance was achieved at 6% limestone powder replacement, which produced a slump flow diameter of 600 mm and compressive strength of 29.58 MPa, exceeding the design strength target of 25 MPa. Higher replacement levels reduced both workability and compressive strength, with the 15% mixture failing to meet acceptable performance criteria. These findings indicate that limestone powder can be effectively utilized as a sustainable partial cement replacement in SCC at moderate replacement levels while maintaining satisfactory fresh and hardened properties.